The Role of Planned Behavior in Predicting Customer Orientation - Hasanbarog Zhila Mahrooz; Rasouli Eshaq; Ardabili Farzad Sattari; Azadi Behnam (Management, 2022)
The purpose of this qualitative research was to investigate the role of planned behavior in predicting customer orientation in the Iranian gas industry. The participants were 17 experts from the National Iranian Gas Company who were selected using purposive sampling and based on theoretical saturation. Data were collected using in-depth semi-structured interviews and were analyzed using thematic analysis and MAXQDA software. The results showed that attitude toward behavior (favorable behavior, pleasant behavior, behavior appraisal), subjective norms (peer pressure, family pressure, social pressure), perceived behavioral control (past experience, anticipation of future events, environmental norms), knowledge (up-to-date knowledge, behavior-related knowledge, education), ethical norms (responsibility, ethical principles, resilience), and discipline (organization, order, streamlining) are important components in predicting customer orientation in the gas industry. The results can help managers in the energy sector to improve their customer orientation and performance through planned behavior.